Pengaruh Literasi Digital dan Self-Efficacy terhadap Kemampuan Berpikir Kritis Ekonomi Siswa SMA dalam Pembelajaran Berbasis Proyek - Primawati Sinaga; Christina Hotma Tondini Turnip; Krisna Sarinauli Lumbansiantar; Muhammad Bukhori Dalimunthe; Deni Adriani (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study was motivated by the low economic critical thinking skills of high school students in the digital era and the importance of digital literacy and self-efficacy as internal influencing factors, particularly within the context of Project-Based Learning (PjBL). The purpose of this study was to analyze the partial and simultaneous effects of digital literacy and self-efficacy on students’ economic critical thinking skills. A quantitative ex-post facto survey approach was employed. The sample comprised 90 high school students in Medan City, randomly selected from three schools that implemented PjBL in economics subjects. Data were collected using a Likert-scale questionnaire to measure digital literacy and self-efficacy, along with an essay test to assess economic critical thinking skills. Data analysis utilized simple and multiple linear regression at a significance level of 0.05. The results revealed that: (1) digital literacy had a positive and significant effect on economic critical thinking skills (β = 0.526, p < 0.05); (2) self-efficacy had a positive and significant effect on economic critical thinking skills (β = 0.489, p < 0.05); and (3) simultaneously, digital literacy and self-efficacy had a positive and significant effect on economic critical thinking skills (F = 29.517, p < 0.05), contributing 40.4% to the variance. It is concluded that digital literacy and self-efficacy are important predictors that synergistically enhance students’ economic critical thinking skills within the Project-Based Learning framework.